Occurrence of antibiotic-resistant Staphylococcus aureus in some street-vended foods in Ogun State, Nigeria - Bello, Olorunjuwon Omolaja; Bello, Temitope Kudirat; Bankole, Samuel Adegoke (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Food borne illnesses of microbial origin are a major international health problem associated with food safety and an important cause of death in developing countries. This study was carried out to investigate the occurrence of antibiotic-resistant Staphylococcus aureus in some street-vended foods in Ogun State, Northwerstern Nigeria. A total of 140 street-vended food samples which included 20 samples each of fish sausages, meat sausages, fried fish, fried meat, fried yam, moin-moin and jollof rice were purchased from vendors in three different communities (Sabo, Isale-Oko and Makun) in Sagamu, Ogun State, Nigeria. Demographic survey was carried out on the hygienic and safety attitudes cultivated by the vendors recruited for this study. Microbiological analyses were carried out on the food products to isolate typical S. aureus strains. The samples were serially diluted and dilution factors of up 10-6 were cultured on Mannitol salt agar medium employing the spread plate technique. The disc-diffusion method was employed to determine the antibiotic resistance patterns of the isolated S. aureus strains. Most vendors were aware of the heath risk associated with unhygienic practices. Percentage products contaminated ranged from 0%, as obtained from fried yam, to 40% obtained from fish sausages. Prevalence of S. aureus strains obtained from samples ranged from 0 (as in fried yam) to 5.20 + 1.2 cfu ml-1 (as obtained from jollof rice). The isolates were subjected to antibiotic susceptibility assay employing the disc diffusion technique. Results on the resistance patterns of the isolated S. aureus strains revealed that resistance was highest to gentamycin (45.8%) and lowest to cotrimoxazole (4.2%) and erythromycin (4.2%). In conclusion, street vended food samples are frequently contaminated with S. aureus and that these could serve as potential vehicle for the transmission of resistant strains of the pathogen. Increased resistance of S. aureus to certain broad spectrum antibiotics such as gentamicin and amoxicillin should stimulate the interest of researchers. Â 